2022
DOI: 10.3389/fvets.2022.1008107
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of BVDV-1a, 1m, and 1v strains from diarrheal calf in china and identification of its genome sequence and cattle virulence

Abstract: Bovine viral diarrhea virus (BVDV) is an important livestock viral pathogen responsible for causing significant economic losses. The emerging and novel BVDV isolates are clinically and biologically important, as there are highly antigenic diverse and pathogenic differences among BVDV genotypes. However, no study has yet compared the virulence of predominant genotype isolates (BVDV-1a, 1b, and 1m) in China and the emerging genotype isolate BVDV-1v. The serological relationship among these genotypes has not yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 78 publications
(133 reference statements)
0
6
0
Order By: Relevance
“…Subsequently, the genotype BVDV-1.19 (1g), with a mean divergence value in the genus of 3.5 bp, was renamed 1.20, and the genotypes BVDV-1.20 (1l or x), BVDV-1.21 (1u), BVDV-1.22 (1k), and BVDV-1.23, with a divergence in the genus higher than 5 bp, were renamed as 1.22, 1.23, 1.24, and 1.25. Details of the computing of divergence values (exceeding limit value 9 for genotype determination) based on 5′-UTR secondary structure sequence alignment of BVDV-1 bovine strains EN-6, T4-32, T4-31-2, GA190608, BJ09_26, HY-3, and HN1626, HB-03, XH-1, MF-3 and one goat strain JS12/02, reported as genotype 1o or 1v isolated from China ( Mao et al , 2016 ; Deng et al , 2020 ; Shi et al , 2020 ; Tian et al , 2021 ; Zhu et al , 2022 ; strain T6-18, reported as genotype 1w isolated from China ( Deng et al , 2020 ), strains TY8723, TR-Erz-Pst8, TRElz-4-2021, TR-Elz-Pst16, IRTV1, and IR-Shiraz-322, reported as genotype 1a, 1l, or 1v, isolated from Turkey and Iran ( Oguzoglu et al , 2019 ; Timurkan and Aydin, 2019 ; clustered according to PNS method as 1.7.3, 1.19, and 1.21, respectively are presented in Supplementary Material 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, the genotype BVDV-1.19 (1g), with a mean divergence value in the genus of 3.5 bp, was renamed 1.20, and the genotypes BVDV-1.20 (1l or x), BVDV-1.21 (1u), BVDV-1.22 (1k), and BVDV-1.23, with a divergence in the genus higher than 5 bp, were renamed as 1.22, 1.23, 1.24, and 1.25. Details of the computing of divergence values (exceeding limit value 9 for genotype determination) based on 5′-UTR secondary structure sequence alignment of BVDV-1 bovine strains EN-6, T4-32, T4-31-2, GA190608, BJ09_26, HY-3, and HN1626, HB-03, XH-1, MF-3 and one goat strain JS12/02, reported as genotype 1o or 1v isolated from China ( Mao et al , 2016 ; Deng et al , 2020 ; Shi et al , 2020 ; Tian et al , 2021 ; Zhu et al , 2022 ; strain T6-18, reported as genotype 1w isolated from China ( Deng et al , 2020 ), strains TY8723, TR-Erz-Pst8, TRElz-4-2021, TR-Elz-Pst16, IRTV1, and IR-Shiraz-322, reported as genotype 1a, 1l, or 1v, isolated from Turkey and Iran ( Oguzoglu et al , 2019 ; Timurkan and Aydin, 2019 ; clustered according to PNS method as 1.7.3, 1.19, and 1.21, respectively are presented in Supplementary Material 1 .…”
Section: Resultsmentioning
confidence: 99%
“…While genotype 1.19 (1w) constituted a separate group in the species, reported in China more recently in 2017 ( Deng et al , 2020 ), the Chinese group of strains reported as 1v ( Deng et al , 2020 ; Tian et al , 2021 ; Zhu et al , 2022 ) and those reported as 1o and considered as 1v ( Shi et al , 2020 ; was related to genotype 1.7 (1o) and constituting a new sub genotype (1.7.3). This corresponded to the observation made by Shi et al (2020) , who reported nine Pestivirus A isolates as putative new 1o sub genotype, based on phylogenetic analysis of partial 5′-UTR and Npro sequences.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The cp BVDV is characterized by the constructive expression of NS3, while ncp BVDV strains produce a fusion of NS2 and NS3 proteins named NS2-3 ( Darweesh et al., 2015 ). BVDV infection causes variable symptoms including growth retardation, hemorrhaging, respiratory and gastrointestinal disorders, reproductive failures, persistent infection, and lethal mucosal disease (MD) ( Mirosław et al., 2022 ; Zhu et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…This classification accurately reproduces the subtyping of all the 118 BVDV-1 and 88 BVDV-2 complete/near-complete genomes (CNCGs) from GenBank (Mucellini et al, 2023). BVDV is classified into three genotypes, BVDV-1 (Pestivirus A), BVDV-2 (Pestivirus B), and BVDV-3 (Pestivirus H or HoBi-like virus), in which BVDV-1 currently contains at least 22 subtypes (1a-1v) and BVDV-2 contains at least 4 subtypes (2a-2d) (de Oliveira et al, 2021;Zhu et al, 2022). The single ORF encodes a large polyprotein that is post-translationally cleaved into four structural proteins (C, E rns , E1, E2) and eight non-structural proteins (N pro , p7, NS2, NS3, NS4A, NS4B, NS5A, NS5B) in ncp BVDV isolates (Chi et al, 2022).…”
mentioning
confidence: 99%